OYUN YÖNTEMİYLE TARİH ÖĞRETİMİNİN ÖĞRENCİ ERİŞİSİNE VE KALICILIĞA ETKİSİ - Gülin KARABAĞ; Okan AYDOĞAN (Turkish History Education Journal, 2015)
The aim of this study is to determine the effect of history teaching with game method on students’ achievement and retention level in comparison with traditional method. This study is limited with units of “The science of History” , “The Rise of Civilization and The First Civilizations” and “The First Turkish States” in 9th grade history curriculum. The research group of this study consists of 57 students who are attending 9th grade (9-C and 9D) of Havza Anatolian High School in Samsun. In this research, quasi-experimental method was used by applying pre-test, post-test and retention test. During the teaching process, determined units are taught to the experimental group with educational games and to the control group with traditional method. According to the obtained findings, there is a significant difference between the points of achievement and retention level of the experimental group and the control group. As a result, it is evaluated that history teaching with game method is more effective than traditional method not only increasing the achievement level but also retention level of the students